Regeneration of Sub-Saharan Africa’s open market places: a case for Guileless stakeholder participation (Construction Economics and Building, 2020)
Sub-Saharan Africa’s urban culture makes open marketplaces an essential part of life in their cities. What goes on in these markets undoubtedly opens them up to threats of adversity, tragedy, and other significant sources of stress. How can these open marketplaces be regenerated into resiliently sustainable places? From a case study of the regeneration redevelopment of the largest open-air market in West Africa i.e. Kumasi Central Market, the need for stakeholder participation in the entire regeneration process is emphasised. The determination of the most important stakeholders during the regeneration of the market is followed by a comparison of the regeneration process regeneration with the literature on urban regeneration, sustainable development, participation, and project management. Lessons learned, and the concerns raised by major stakeholders in the process creates certain project management approaches essential for achieving resilient urban regeneration. Identification of all important stakeholders by the consideration of their attributes of power, legitimacy and urgency and distrustfully engaging all stakeholders is vital to the success of any urban regeneration project.